Polyphenol-based design of functional olive leaf infusions - Peršurić, Željka; Saftić, Lara; Klisović, Dora; Kraljević Pavelić, Sandra (2019)
The beneficial properties of polyphenols are widely recognized, and polyphenol-rich olive oil, which is part of the typical Mediterranean diet, has been identified as having positive health effects. However, over the past decade, olive leaves have been discovered as an alternative polyphenol-rich source. This is particularly interesting in the context of the growing interest in functional foods, as well as in terms of the management of biological waste, including olive leaves that are left over from the production of olive oil. Previous studies on olive leaves confirmed that they have a high phenolic content, which explains their previously described strong antibacterial, antimicrobial and antiviral activity. Therefore, the major aim of our work is to comprehensively determine olive leaf phenolic content in cultivars Istarska bjelica, Leccino and Buža as a natural source of bioactive compounds suitable for daily consumption in the form of infusion. For this purpose, we examined the influence of olive leaf cultivar, maceration time and temperature on the phenolic composition of final infusions. Phenolic compounds were analysed by liquid chromatography (LC) coupled to a triple quadrupole mass spectrometer (LC-QQQ). As expected, the results indicate the significant influence of not only the olive cultivar but also of maceration parameters on the qualitative and quantitative phenolic composition. The highest phenolic compound content was obtained in the infusion of Istarska bjelica leaves after 15 min of maceration. However, the Buža olive leaf infusion had the most diverse phenolic composition. Furthermore, we designed several functional olive leaf infusion mixtures with phenolic compositions adjusted based on the desired health effect. The results show the role of phenolic composition adjustment in the development and improvement of the quality of functional olive leaf infusions.
Blagotvorna svojstva polifenola su općepoznata. Utvrđeno je da maslinovo ulje, tipična namirnica u mediteranskoj prehrani, ima velik udjel polifenola te širok spektar pozitivnih učinaka na ljudsko zdravlje. Međutim, tijekom proteklog desetljeća, ustanovljeno je da i lišće maslina može biti alternativni izvor polifenolnih spojeva iz masline. To je osobito zanimljivo u kontekstu rastućeg interesa za funkcionalnu hranu, kao i iskorištenja biološkog otpada. Prethodne studije na lišću maslina potvrdile su da ima velik udjel fenola, što objašnjava njihovu dokazanu jaku antibakterijsku, antimikrobnu i antivirusnu aktivnost. Stoga je glavna svrha našeg rada bila ispitati sadržaj fenola u lišću maslina sorti Istarska bjelica, Leccino i Buža, kao prirodnih izvora bioaktivnih spojeva pogodnih za dnevnu potrošnju u obliku čaja (biljne infuzije). U tu je svrhu analiziran utjecaj sorte maslinovog lišća, vremena maceracije i temperature na fenolni sastav dizajniranih čajeva. Analiza fenolnih spojeva provedena je pomoću tekućinske kromatografije (LC) spregnute s trostrukim kvadrupolnim masenim spektrometrom (LC-QQQ). U skladu s pretpostavkama istraživanja, rezultati pokazuju znatan utjecaj sorte masline i parametara maceracije na kvalitativni i kvantitativni fenolni sastav. Najveći udjel fenolnih spojeva dobiven je u biljnoj infuziji sorte Istarska bjelica nakon 15 minuta maceracije. Međutim, biljna infuzija sorte Buža imala je najraznolikiji fenolni sastav.
Bibliografija: 49 jed.
Summary ; Sažetak.
Keywords: Maslina -- Lišće masline -- Polifenoli